The impact of impending credit rating change on managerial voluntary disclosure - He, Guanming (2013)
This study investigates whether and how managers commit to voluntary disclosure to maintain or achieve a desired credit rating during an impending credit rating change. I find that firms near a rating change are more likely to publicly release product and business expansion information to increase information transparency but no evidence of a higher incidence of an earnings forecast. The positive impact of impending rating change status on managerial propensity to disclose the nonfinancial information is more evident for firms that are subject to low proprietary cost of the disclosure. I find no evidence that credit ratings are manipulated via the voluntary disclosure. In particular, firms close to a rating change do not selectively release good news on their product and business expansion information. Nor do the firms likely issue a good news earnings forecast, an optimistic forecast or a more precise forecast for good news than for bad news. Overall, the results suggest that firms generally exhibit a credible commitment to increasing disclosure transparency for a desired credit rating. Further analysis reveals that an increase in the nonfinancial disclosure raises the likelihood of a rating upgrade in the subsequent period.